Exploring the reaction dynamics of alanine racemase using serial femtosecond crystallography - Jihan Kim; Jaehyun Park; Keondo Lee; Wan Kyun Chung; Ki Hyun Nam; Yunje Cho (Scientific Reports)
Abstract Alanine racemase (Alr) catalyzes the pyridoxal 5′-phosphate (PLP)-dependent racemization between l- and d-alanine in bacteria. Owing to the potential interest in targeting Alr for antibacterial drug development, several studies have determined the structures of Alr from different species, proposing models for the reaction mechanism. Insights into its reaction dynamics may be conducive to a better understanding of the Alr reaction mechanism. In this study, we determined the structures of the apo and reaction states of Bacillus subtilis Alr (BsAlr) at room temperature using a fixed-target based X-ray free-electron laser. The 2.3 Å resolution structures revealed the alanine substrate or intermediate in various positions at the active site. Conformational change between the N- and C-terminal domains of BsAlr expanded the entryway for substrate binding. In the reaction state of BsAlr, two main alanine binding states were observed: one alanine molecule is positioned away from PLP, whereas the other alanine molecule is covalently bonded to PLP. These structures might represent the dynamic states of the substrate for entrance into, reaction with, or exit from the active site. Our approach provides a simple and rapid method for elucidating the intermediate structure of Alr, which can be expanded to other enzymes.